CONSUMER SATISFACTION TOWARDS GOOGLE PAY SERVICES IN THE MALAPPURAM DISTRICT - M, Abdurahman; PP, Jayaprakasan; Noushad Kt (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Digital payment systems have revolutionized financial transactions worldwide, with Google Pay emerging as a prominent platform for contactless and peer-to-peer payments. This study examines consumer satisfaction with Google Pay in Malappuram District, Kerala, focusing on user awareness, usage patterns, key purposes of transactions, and associated challenges. The research is based on primary data collected through a structured questionnaire from 62 respondents, supplemented by secondary data sources. Findings indicate that Google Pay usage has increased significantly post-demonetization and post-COVID-19 pandemic. The majority of users are young, well-educated, and primarily students. Fund transfers, shopping, food ordering, and bill payments are among the most common uses of the platform. Consumers expressed high levels of satisfaction regarding user-friendliness, transaction speed, and security features. However, certain concerns remain, such as customer support services and grievance redressal mechanisms. The study highlights the growing acceptance of digital payment solutions and provides insights into improving the user experience and addressing existing challenges. These findings can aid financial institutions and policymakers in enhancing digital payment adoption and customer satisfaction.